Agriculture, trade, and the WTO : creating a trading environment for development - Ingco, Merlinda D. (Washington, D.C. : World Bank, 2003)
There are a number of policy interventions applied in industrial and developing countries that impact world trade and production in agriculture. This report addresses such issues as the lessons learned from the Uruguay Round of negotiations which can be applied to the next round of negotiations.
Papers presented at a conference held in July 2001 and sponsored by the World Bank.
Includes bibliographical references and index.
oif 16/09/15
Loan
Keywords: Agriculture; Produce trade - government policy; Agriculture and state; Food industry and trade; Developing countries; Developing countries